Theory and design of seismic resistant steel frames - Mazzolani, Federico M (Spon, 1996)
Theory and Design of Seismic Resistant Steel Frames is a state-of-the-art summary of recent developments in the behaviour, analysis and design of seismic resistant steel frames. The book provides advanced students, researchers and professionals in civil and structural engineering with the basic principles upon which the modern seismic codes are based. It deals with all recent developments in seismic design of steel